Stable isotope compositions of speleothems from the last interglacial – Spatial patterns of climate fluctuations in Europe. (1st April 2017) - Demény, Attila; Kern, Zoltán; Czuppon, György; Németh, Alexandra; Leél-Őssy, Szabolcs; Siklósy, Zoltán; Lin, Ke; Hu, Hsun-Ming; Shen, Chuan-Chou; Vennemann, Torsten W.; Haszpra, László
Abstract: Studies on the last interglacial (LIG) can provide information on how our environment behaved in a period of slightly higher global temperatures at about 125 ± 4 ka, even if it is not the best analogue for the Holocene. The available LIG climate proxy records are usually better preserved and can be studied at a higher resolution than those of the preceding interglacials, allowing detailed comparisons. This paper presents complex stable hydrogen, carbon and oxygen isotope records obtained for carbonate (δ 13 C and δ 18 Ocarb ) and fluid inclusion hosted water (δD and δ 18 Ow ) of a stalagmite from the Baradla Cave system in Central Europe that covers most of the LIG, as proven by U-Th dates. Comparing its C and O isotope data with records reported for other speleothem (cave-hosted carbonate) deposits from Europe revealed the complex behavior of these climate proxies, with a concerted relative increase in 18 O of carbonates from 128 to 120 ka and synchronized shifts in the opposite direction after 119 ka. The hydrogen isotope analyses of inclusion-hosted water extracted from the BAR-II stalagmite also correspond to the regional climate proxy records, with meaningful deviations from global temperature trends. Beside following the general paleotemperature pattern from the climate optimum (high δD values up to −64‰ around 120 ka) to the subsequent cooling starting at about 119 ka (low δD values down to −90‰ at about 109 ka), a period between 126.5 and 123 ka with low δD values (down to −81‰) is detected in the BAR-II stalagmite. Although the isotope shifts are muted in the C-O isotope data of carbonate due to competitive fractionation processes, the δ 13 C data show a positive relationship with the δD pattern, indicating humidity – and possibly temperature – variations. The periods with low δD values fit well to temperature and humidity changes inferred from proxy records from western Europe to the eastern Mediterranean. Spatial distributions of these variables show, that at about 125 ± 2 ka the Mediterranean region was characterized by warm, humid conditions and enhanced seasonality with elevated winter precipitation. The combined interpretation of stable isotope data revealed that the Alpine and Mediterranean regions behaved differently during Greenland Stadial 26 (GS26, ∼119 to 116.2 ka). While the Alpine records fluctuated in close agreement with the Central Greenland ice core δ 18 O data, the BAR-II stalagmite show a positive δ 18 Ocarb anomaly. The Baradla data indicate enhanced aridity and seasonality for a part of GS26, with the relative dominance of summer precipitation and Mediterranean moisture contribution. Following the GS26 event, the effect of long-term global cooling becomes dominant in the Baradla isotope records and leads to glacial inception at about 109 ka. Highlights: Stable isotope compositions of a last interglacial (LIG) stalagmite, Central Europe. A sequence of climate change events during the LIG for European speleothems. Hydrogen isotope data of inclusion water reveal a major event at about 125 ± 2 ka. Temperature and winter precipitation changes around the Mediterranean at 125 ± 2 ka.